Pola Komunikasi Alumni Santri Pondok Pesantren Musthafawiyah dalam Membangun Sosial di Universitas Islam Negeri Sumatera Utara Medan - Tohari, Adrian Roihan (YASIN, 2023)
Communication patterns are one of the fundamental aspects of communication in social development and can be used by anyone, including alumni of musthafawiyah students. The objectives of this research are (1) to find out the communication patterns of alumni of musthafawiyah students in social development at the State Islamic University of North Sumatra, Medan. (2) To find out what things alumni of musthafawiyah students do in social development at the North Sumatra State Islamic University of Medan. (3) To find out the connecting and inhibiting factors of communication patterns of musthafawiyah alumni students in social development at the State Islamic University of North Sumatra, Medan. The type of research used in this research is qualitative research with a descriptive approach. Data obtained through interviews, observation, and documentation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. This research was conducted at the State Islamic University of North Sumatra, Medan. The results of this study indicate the objective condition of the communication patterns used by the alumni of the musthafawiyah students while still at the musthafawiyah Islamic boarding school and when they were already at the Medan North Sumatra State Islamic University, as well as the role of the IMA KAMUS Medan organization in helping alumni of the musthafawiyah students in social development at the Islamic university the land of north sumatra field. The things that the alumni of the musthafawiyah students do in social development, as well as the connecting and inhibiting factors of the communication patterns of the musthafawiyah santri alumni in building socially at the Medan State Islamic University of North Sumatra.